PENGENDALIAN PERSEDIAAN BAHAN BAKU BASE MATERIAL PADA INDUSTRI KERAMIK DI PT. XYZ - Lidya Susanti; Machfud Machfud; Rokhani Hasbullah (School of Business, Bogor Agricultural University (SB-IPB), 2015)
Inventory of raw materials in the company is very important, so it has to be controlled. A good inventory control of raw materials should be supported with cost efficiency. This study was to analyze factors that cause the base material inventories excess at PT. XYZ and analyze the purpose of the base material inventories to be controlled. The reseacrh was using a fish bone method and continue with using pairwise comparison method assisted with the expert choice 2000 software. The classification result based on ABC analysis, the selected item that was going to be analyzed was the A category items.The items that are included in the A category are clay ex belitung jw, clay ja 1/ja b and sodium feldspar. The EOQ equations model was used to answer the purpose of the base material inventories control. Based from the EOQ model, the needed quantity, order quantity, order frequency, reorder point (ROP), total order cost (TOC), total carrying cost (TCC), and total inventory cost (TIC) could be obtained. The comparison of the total cost of inventory among the EOQ model and company policies showed that the EOQ model in seven months can save up to Rp311.612.769. PT. XYZ could minimize the base material inventory costs by calculating the costs incurred. The EOQ model could be implemented if all of the departments involved are well cooperated. PT. XYZ should also be able to make inventory control standards which are quantity order, order frequency, and reorder point. Keywords: Cost, EOQ, frequency, inventory, ROPABSTRAKPersediaan bahan baku pada perusahaan sangatlah penting, sehingga harus dapat dikendalikan. Pengendalian persediaan bahan baku yang baik harus didukung dengan efisiensi biaya. Penelitian ini untuk menganalisis faktor-faktor yang menyebabkan kondisi persediaan bahan baku base material berlebih di PT. XYZ dan menganalisis persediaan bahan baku base material agar dapat dikendalikan. Penelitian ini menggunakan metode fish bone dilanjutkan dengan metode pairwise comparison dengan dibantu software expert choice 2000. Hasil pengklasifikasian berdasarkan analisis ABC item yang akan di analisis yaitu item yang termasuk klasifikasi A. Item yang termasuk klasifikasi A yaitu clay ex belitung jw, clay ja 1/ja b dan sodium feldspar. Persamaan-persamaan model Economic Order Quantity (EOQ) digunakan untuk menjawab tujuan dari pengendalian persediaan bahan baku base material. Pada model EOQ didapatkan jumlah kebutuhan, banyaknya jumlah setiap pemesanan, frekuensi pemesanan, titik pemesanan ulang (ROP), total biaya pesan (TOC), total biaya simpan (TCC) dan total biaya persediaan (TIC). Hasil perbandingan total biaya persediaan antara model EOQ dan kebijakan perusahaan didapatkan hasil bahwa dengan menggunakan model EOQ dalam tujuh bulan dapat menghemat Rp311.612.769. PT. XYZ dapat meminimalkan biaya persediaan bahan baku base material dengan melakukan perhitungan biaya-biaya yang ditimbulkan. Model EOQ dapat dijalankan ketika semua Departemen yang terlibat dapat bekerjasama dengan baik. PT. XYZ pun harus dapat membuat standar pengendalian persediaan yaitu jumlah setiap kali pemesanan, frekuensi pemesanan, titik pemesanan ulang. Kata kunci: Biaya, EOQ, frekuensi, persediaan, ROP